A study of radio astronomy principles and SKA pathfinder system designs with pulsar science - Otto, Sunelle (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2011.